TO EVALUATE THE EFFECT OF INTRAVITREAL INJECTION OF TRIAMCINOLONE ACETONIDE IN RECALCITRANT MACULAR DISORDERS. - Jain, Amit K; Jain, Seema; Pandey, Dadan Ji; Sharma, Rajkumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Recalcitrant macular disorders are those retinal conditions which, though treated by various medical and surgical modalities, but showed no improvement in symptoms or visual acuity or both. The present study was carried out to evaluate the efficacy of intravitreal triamcinolone acetonide (TA) injection in patients with these recalcitrant macular disorders. Methods: This prospective and interventional study included 40 patients (40 eyes) having recalcitrant macular disorders. Complete ophthalmic examination such as measurement of intraocular pressure (IOP), visual acuity (log minimal angle of resolution [MAR] units), fundus photography with fluorescein angiography were carried out before and after intravitreal injection of TA. The patients received an intravitreal injection of TA (10 mg) for diabetic macular edema (n=14), age-related macular degeneration (n=13), pars plana cystoid macular edema (CME) (n=5), vascular diseases (n=3), central chorioretinopathy (n=3), and idiopathic CME (n=2). The follow-up was done on day 1, day 7, 1 month, 2 month and 4-month intervals. Results: The mean visual acuity at 2 months (1.12±0.45 log MAR units), and 4 months (1.08±0.46 log MAR unit) after the injection were significantly better than baseline measurements (1.32±0.3 log MAR units). The mean baseline IOP was 12.5±2.9 mmHg. The IOP significantly increased after the injection at day 1 and day 7; however, the change in IOP at 1 month, 2 months, and 4 months was not statistically significant. Conclusion: The results indicate that intravitreal injection of TA in patients with recalcitrant macular disorders caused significant improvement of visual acuity in 10 mg dose. Keywords: Intravitreal triamcinolone acetonide, Macular edema, Visual acuity, Intraocular pressure.